In Vitro And In Vivo Phenotypic Studies To Characterize Blastocystis Sp. Subtype 3 (ST3) Isolated From Asymptomatic Individuals, Symptomatic And Irritable Bowel Syndrome (IBS) Patients / Nanthiney Devi Ragavan - Nanthiney Devi, Ragavan (2016)
The role of intestinal infection mediated-inflammation in the pathogenesis of irritable bowel syndrome (IBS) remains uncertain. Blastocystis sp. is the most common gut parasite found in the intestinal tract of humans. Its association with IBS is controversial, possibly as a result of irregular shedding of parasites in stool. The study aimed to screen for Blastocystis sp. in stool aspirate and stool samples in adult patients with and without IBS undergoing colonoscopy and measure the interleukin levels (IL-3, IL-5 and IL-8). This study suggests that stool aspirate sample may be a better method for sample collection for detecting Blastocystis sp. by PCR method during colonoscopy. Subtype 3 (ST3) was found to be the most predominant subtype. An increase in the interleukin levels demonstrates that Blastocystis sp. does have an effect in the immune system. The phenotypic characteristics of Blastocystis sp. ST3 isolated from asymptomatic individuals, symptomatic and irritable bowel syndrome (IBS) patients were analyzed. Blastocystis sp. ST3 isolated from IBS patients was shown to have a distinct growth profile, strong aggregation and clumping of parasites when stained with Modified Fields’ stain with outer surface showing a greater binding affinity towards FITC Con A in symptomatic than asymptomatic isolates. Ultrastructural studies also showed that the parasite isolated from IBS patients possesses a rough, coarse surface with thicker surface coat and the presence of electron dense material. Ileum from the rabbit and Balb/C mice showed the highest number of muscle twitching when introduced with Blastocystis sp. ST3 antigen (Blasto-Ag ST3) derived from Blastocystis sp. infected IBS patient. The present study is the first to demonstrate the phenomenon of gut environment facilitating adaptation of parasites possibly for survival leading to phenotypic differences for Blastocystis sp. within a particular subtype. An in vitro model to study the pathogenicity of Blastocystis sp. ST3 was designed by comparing the iv degree of mucosal sloughing, inflammation and necrosis of tissue of the Wistar rat’s ileum, caecum, colon and rectum orally inoculated with Blastocystis sp. ST3 cysts isolated from asymptomatic individuals, symptomatic and IBS patients. This is the first study to provide evidence that occurrence of mucosal sloughing, inflammation and necrosis was seen to be higher in IBS group compared to symptomatic and asymptomatic group. This study supports the earlier findings that intestinal inflammation does play an important role in the clinical manifestation of IBS patients. With this, the association between Blastocystis sp. infection and inflammation was investigated. Wnt signaling pathway had been linked with inflammation and colorectal cancer. In the present study, we attempted to assess the effects Blasto-Ag derived from non-IBS and IBS patients respectively on the growth and gene expression of cancer cells, HCT116 in vitro compared with normal cells, CCD-18Co. The results revealed that the proliferation rate and migration of cells for both normal and cancer cells were significantly higher when induced with IBS Blasto-Ag ST3 compared to non-IBS Blasto-Ag ST3 implying that it may play a role in advancing colorectal tumor progression in IBS patients. Wnt analysis showed that a large number of canonical Wnts involved in the canonical pathway for both normal and cancer cells upon exposure of both the non-IBS and IBS Blasto-Ag ST3. However, IBS Blasto-Ag ST3 showed a greater effect on both cells compared to non-IBS Blasto-Ag ST3. The present study also conclusively provides evidence for the first time the factors such as the frequency of toilet visit in a day, the timing of toilet visit, the stool forms, and patient’s moods as well as emotions can influence the shedding pattern of Blastocystis sp. cysts in an IBS patient. Stools should be collected in the morning; especially samples should be taken from the semi-solid form every time one visits the toilet even within a day for diagnostic purposes.